DISTRIBUSI DAN KELIMPAHAN IKAN KARANG FAMILI POMACENTRIDAE DI PERAIRAN TERUMBU KARANG DESA POOPOH KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Ari B. Rondonuwu; John L Tombokan; Unstain NWJ Rembet (Jurnal Ilmiah PLATAX, 2013)
DISTRIBUSI DAN KELIMPAHAN IKAN KARANG FAMILI POMACENTRIDAE DI PERAIRAN TERUMBU KARANG DESA POOPOH KECAMATAN TOMBARIRI KABUPATEN MINAHASA Distribution and Abundance of Coral Fishes the Family Pomacentridae in Coral Reef Waters Poopoh Village Sub-District Tombariri Minahasa Regency Ari B Rondonuwu1, John L Tombokan1, Unstain NWJ Rembet1   ABSTRACT This study aims to determine the distribution and abundance of reef fish (families Pomacentridae) in coral reef waters of Poopoh village District Tombariri.  This study was conducted at 3 stations. Data collected was done using visual census on the 50-meter transect line at 3 meters and 10 meters depths. In addition to revealing the number of species and abundance of individuals Pomacentridae, data analysis aimed to determine the community index. Based on the identification, obtained 41 species from 12 genera. 4 species has its presence in large numbers in all three observation stations, Chromis margaritifer, Pomacentrus mollucensis, Chrysiptera unimaculata, and the species with the largest number of individuals that is Chromis ternatensis. Based on depth, found 35 species with a total of 3863 individuals at a depth of 3 meters and 36 species at a depth of 10 meters with a total of 3810 individuals. Pomacentridae fish species diversity index ranged between 2.181-2.857. Dominance Index, are categorized low in the range of 0.081-0.197.. Keywords : coral fishes, Pomacentridae, coral reef, Poopoh   ABSTRAK Penelitian ini bertujuan untuk mengetahui distribusi dan kelimpahan ikan karang famili pomacentridae  di perairan terumbu karang Desa Poopoh Kecama-tan Tombariri. Penelitian dilakukan di 3 lokasi. Pengambilan data dilakukan dengan metode sensus visual pada transek garis sepanjang 50 meter, kedalaman 3 meter dan 10 meter. Selain mengungkapkan jumlah spesies dan kelimpahan individu Pomacentridae, analisis data diarahkan untuk mengetahui indeks komunitas. Berdasarkan hasil identifikasi, diperoleh 41 spesies yang berasal dari 12 genera. 4 spesies kehadirannya dalam jumlah yang besar di ketiga stasiun pengamatan yaitu, Chromis margaritifer, Pomacentrus mollucensis, Chrysiptera unimaculata, dan spesies dengan jumlah individu terbesar yaitu Chromis ternatensis. Berdasarkan kedalaman, ditemukan 35 spesies dengan total 3863 individu pada kedalaman 3 meter dan 36 spesies di kedalaman 10 meter dengan jumlah total 3810 individu.  Indeks keanekaragaman spesies ikan Pomacentridae berkisar antara 2.181-2.857. Indeks dominasi, dikategorikan rendah pada kisaran 0.081- 0.197.   Kata kunci : ikan karang, Pomacentridae, terumbu karang, Poopoh       1 Laboratorium Pengelolaan Pesisir Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi